Morphology of lungs in pulmonary lymphangioleiomyomatosis – A unique case of bilateral lungs and heart transplant - Shirish Sahebrao Chandanwale; Yaminy Pradeep Ingale; Payal Patel; Anubhaw Verma (Indian Journal of Transplantation, 2023)
Pulmonary lymphangioleiomyomatosis (LAM) is an extremely rare low–grade neoplasm. It occurs either sporadically or with tuberous sclerosis complex. Sporadic type usually affects women in reproductive age group. The patient usually gives a history of dyspnea of long duration. With characteristic clinical findings including high-resolution computed tomography findings, a diagnosis of pulmonary LAM can be suspected. Histopathology findings in some cases can be subtle. Cells of LAM consistently express smooth muscle markers such as smooth muscle actin and desmin on immunohistochemistry. Cells also express melanocytic marker such as HMB-45, Melan-A, and microphthalmia transcription factor. Due to the scarcity of reports on morphological features in pulmonary LAM, we are tempted to report morphological features of lungs in a 36-year-old female who successfully underwent bilateral lung and heart transplant at a tertiary care center.